2018
DOI: 10.1155/2018/4269798
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Ultrasound Transbronchial Needle Aspiration in Thoracic Diseases: Much More than Mediastinal Staging

Abstract: Background and Objective EBUS-TBNA has revolutionized the diagnostic approach to thoracic diseases from a surgical to minimally invasive procedure. In non small-cell lung cancer (NCSLC) patients, EBUS-TBNA is able to dictate the consecutive therapy both for early and advanced stages, providing pathological diagnosis, mediastinal staging, and even adequate specimens for molecular analysis. This study reports on the ability of EBUS-TBNA to make different diagnoses and dictates the consecutive therapy in a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
4
26
0
1
Order By: Relevance
“…Disease-specific accuracy was 81.7%, 84% and 78.9% in the diagnosis of cancer, NSCLC and non-cancer lesions, respectively. The accuracy achieved was largely comparable with those reported in literature (14)(15)(16)(17). The sensitivities for all pathologies, cancer, NSCLC and non-cancer were 55.1, 48.8, 48.3, and 60%, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Disease-specific accuracy was 81.7%, 84% and 78.9% in the diagnosis of cancer, NSCLC and non-cancer lesions, respectively. The accuracy achieved was largely comparable with those reported in literature (14)(15)(16)(17). The sensitivities for all pathologies, cancer, NSCLC and non-cancer were 55.1, 48.8, 48.3, and 60%, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…In this prospective study, we analysed the first 266 unselected consecutive patients who underwent thoracic endosonography in our centre in a 4‐year study period. Our study showed an overall diagnostic yield of 68.4%, which were in line with previously published evidence reporting a yield between 61% and 92% 4,5,11,34 . A possible explanation that our yield reached the lower end of this range is the study design that included an unselected study population in a real‐world setting.…”
Section: Discussionsupporting
confidence: 91%
“…The searches identified 5,675 results. After screening titles and abstracts, 191 potentially eligible articles remained, of which 14 studies were included in the final analysis [9,[14][15][16][17][18][19][20][21][22][23][24][25][26]. Of these, 3 were conference abstracts.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%